Corporate Governance Country Assessment : Slovak Republic - World Bank (Washington, DC, 2013)
This report provides an assessment of the corporate governance policy framework, and enforcement and compliance practices in the Slovak Republic. Slovakia has already upgraded its legislation to meet European Union (EU) Directives. The legislative and regulatory framework dealing with corporate governance issues has improved. The major issues identified by this review include: 1) the general weakness of the supervisory board, which causes some non-compliance with several of the Organization for Economic Cooperation and Development - OECD - Principles; 2) lack of protection for shareholders of "Free Market" companies, and, 3) inadequate authority and institutional capacity at the Financial Market Authority (FMA). Strengths and weaknesses are highlighted and policy recommendations made where appropriate. The report proposes that an Institute of Directors be created to train supervisory board members, disseminate best practice, and promote dialogue between the public and private sectors. Together, the recommendations give issuers the choice to implement best practice, and for investors a benchmark against which to measure corporate governance in Slovakia.